2022
DOI: 10.1029/2022jc018440
|View full text |Cite
|
Sign up to set email alerts
|

Circumpolar Variations in the Chaotic Nature of Southern Ocean Eddy Dynamics

Abstract: Circulation in the Southern Ocean is unique. The strong wind stress forcing and buoyancy fluxes, in concert with the lack of continental boundaries, conspire to drive the Antarctic Circumpolar Current replete with an intense eddy field. The effect of Southern Ocean eddies on the ocean circulation is significant—they modulate the momentum balance of the zonal flow, and the meridional transport of tracers and mass. The strength of the eddy field is controlled by a combination of forcing (primarily thought to be … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 33 publications
0
14
0
Order By: Relevance
“…Despite the significant amplitude increases of long-lived eddies, as shown herein, the amplitudes of short-lived eddies have changed little. Given shortlived eddies' lifetimes (defined here as between 10 and 90 d), these results may partly reflect the stochastic, chaotic nature of these eddies (Hogg et al 2022) and partly represent changes in eddies with relatively long lifetimes. In addition, much of the existing research has indicated that the ocean is saturated with nonlinear eddies that merge, split, and couple with one another (Grooms 2015).…”
Section: Conclusion and Discussionmentioning
confidence: 99%
“…Despite the significant amplitude increases of long-lived eddies, as shown herein, the amplitudes of short-lived eddies have changed little. Given shortlived eddies' lifetimes (defined here as between 10 and 90 d), these results may partly reflect the stochastic, chaotic nature of these eddies (Hogg et al 2022) and partly represent changes in eddies with relatively long lifetimes. In addition, much of the existing research has indicated that the ocean is saturated with nonlinear eddies that merge, split, and couple with one another (Grooms 2015).…”
Section: Conclusion and Discussionmentioning
confidence: 99%
“…In fact, the Antarctic Circumpolar Current features large intrinsic variations compared to forced variability, as shown by Hogg et al. (2022).…”
Section: Summary and Concluding Remarksmentioning
confidence: 79%
“…When interpreting the robustness of our results, caution should be taken since results derive from only one realization of a complex system. In fact, the Antarctic Circumpolar Current features large intrinsic variations compared to forced variability, as shown by Hogg et al (2022).…”
Section: Temporal Changesmentioning
confidence: 96%
“…Despite the significant amplitude increases of long-lived eddies, as shown herein, the amplitudes of short-lived eddies have changed little. Given short-lived eddies' lifetimes (defined here as between 10 and 90 days), these results may partly reflect the stochastic, chaotic nature of these eddies (Hogg et al, 2022) and partly represent changes in eddies with relatively long lifetimes. In addition, much of the existing research has indicated that the ocean is saturated with nonlinear eddies that merge, split, and couple with one another (Groom, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…The causes for the long-term changes in the EKE are thought to be due to a strengthening of the wind stress with delays of 1-4 years (Hogg et al, 2015;Menna et al, 2020). Besides external wind-forced changes in the EKE, high-resolution modeling has suggested that the eddy field also exhibited a chaotic internal nature, which may mask wind-driven changes (Meredith, 2016;Patara et al, 2016;Hogg et al, 2022). Another important feature is the spatial pattern of the EKE field, which is collocated with major topography and is primarily determined by the instability of the mean flow (Graham et al, 2012;Barthel et al, 2017;Chapman, 2017;Youngs et al, 2017;Cai et al, 2022).…”
Section: Introductionmentioning
confidence: 99%